2020
DOI: 10.3390/molecules25061414
|View full text |Cite
|
Sign up to set email alerts
|

Unknown Areas of Activity of Human Ribonuclease Dicer: A Putative Deoxyribonuclease Activity

Abstract: The Dicer ribonuclease plays a crucial role in the biogenesis of small regulatory RNAs (srRNAs) by processing long double-stranded RNAs and single-stranded hairpin RNA precursors into small interfering RNAs (siRNAs) and microRNAs (miRNAs), respectively. Dicer-generated srRNAs can control gene expression by targeting complementary transcripts and repressing their translation or inducing their cleavage. Human Dicer (hDicer) is a multidomain enzyme comprising a putative helicase domain, a DUF283 domain, platform,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 49 publications
4
12
0
Order By: Relevance
“…Accordingly, we performed cleavage assays with a 21-nt RNA substrate, called "RNA21". We found that ∆DUF(625-752) generated 15-nt, 6-nt and 2-nt RNA products (Figure 4), as it was earlier observed for hDcr and the hDicer variants lacking the PAZ domain [25]. With incubation time, we observed disappearance of 15-nt and 6-nt RNA products and accumulation of 2-nt RNAs.…”
Section: Rnase Activity Of the Hdicer Duf283 Deletion Variantsupporting
confidence: 80%
See 2 more Smart Citations
“…Accordingly, we performed cleavage assays with a 21-nt RNA substrate, called "RNA21". We found that ∆DUF(625-752) generated 15-nt, 6-nt and 2-nt RNA products (Figure 4), as it was earlier observed for hDcr and the hDicer variants lacking the PAZ domain [25]. With incubation time, we observed disappearance of 15-nt and 6-nt RNA products and accumulation of 2-nt RNAs.…”
Section: Rnase Activity Of the Hdicer Duf283 Deletion Variantsupporting
confidence: 80%
“…This 128-amino acid fragment of hDicer was earlier demonstrated to accelerate base-pairing between two complementary RNA or DNA molecules in vitro [17]. The expression plasmid encoding the hDicer ∆DUF(625-752) variant was produced by a PCR approach using as a template the plasmid encoding the wild-type full-length hDicer fused with the 3xFlagtag (called "hDcr") that was earlier obtained in our laboratory [25]) (Figure 1a,b) (for details please see Materials and Methods). The expression plasmid was used for the transfection of 293T NoDice cells (human cells that do not produce hDicer) [26].…”
Section: Production Of the Hdicer Duf283 Deletion Variantmentioning
confidence: 99%
See 1 more Smart Citation
“…Some paired 19-mers with a dTdT overhang at the 3′ end bind Dicer with high affinity; these sequences are not cleaved by Dicer, are fully transferred to Ago and trigger high-efficiency gene-silencing activity ( Snead and Rossi, 2012 ; Snead et al, 2013 ). Dicer also binds single RNAs at a specific site with high affinity, the function of which is to accelerate hybridization with a partner from the milieu of RNA metabolism ( Kurzynska-Kokorniak et al, 2016 ; Wojnicka et al, 2020 ). This leads to the paradigm that hDicer acts as an annealer and presents a RNA molecule for searching a complementary segment in the RNA degradome, thus facilitating pairing between a small RNA and a complementary longer RNA in asymmetric mode.…”
Section: Resultsmentioning
confidence: 99%
“…It was demonstrated that, in contrast to the PAZ-containing Dicers, which can bind the substrate termini, noncanonical Dicers initiate processing in the interior and work outward [ 100 ]. Moreover, in vitro studies revealed that the PAZ domain deletion variants of hDicer do not process pre-miRNAs and pre-siRNAs; however, they can cleave single-stranded RNA and DNA substrates, and the resulting products differ in size from typical hDicer products [ 104 ]. These results suggest that when the PAZ domain is absent (or not available), other hDicer domains may contribute to substrate binding, and in such cases, noncanonical products can be generated.…”
Section: Dicer Structure and The Importance Of Its Domainsmentioning
confidence: 99%